Intact automatic motor inhibition in attention deficit hyperactivity disorder. (December 2018) - Keute, Marius; Krauel, Kerstin; Heinze, Hans-Jochen; Stenner, Max-Philipp
Abstract: Hyperactivity and impulsivity are defining symptoms of attention-deficit hyperactivity disorder (ADHD), next to inattention. Hyperactive and impulsive behavior in ADHD is often thought to result from a deficit in inhibitory motor control. However, testing for such a deficit is complicated by coexisting deficits in ADHD, specifically an impairment in maintaining task set, e.g., due to inattention. Typical inhibition paradigms, such as Stop-signal, Go/NoGo or Flanker paradigms, are susceptible to a fundamental confound between inhibition and inattention because inhibition is an explicit goal in these tasks. We eliminate this confound by studying the negative compatibility effect (NCE), reflecting a core inhibitory function in the human motor system which, in healthy individuals, inhibits movements automatically, i.e., without deliberation or even conscious awareness. Our behavioral analysis, including Bayesian model comparison, as well as the time-course of the lateralized readiness potential (LRP), consistently show that this function is intact in children with ADHD compared to healthy controls, independent of the presence or absence of prominent hyperactive-impulsive symptoms. We conclude that hyperactivity and impulsivity in ADHD do not result from a low-level deficit in motor inhibition.